Would Renationalisation and Co-financing of the Common Agricultural Policy Be Justified? - Ákos Kengyel (Intereconomics)
Abstract During the past decades several attempts have been made to reform the Common Agricultural Policy (CAP). The article analyses the possible new directions of CAP implementation and financing of the CAP. It discusses whether renationalisation and co-financing of the CAP would be a beneficial approach to make the policy more efficient and to help restructuring not just the CAP expenditure but the whole EU budget. The author analyses the changes in light of the new regulatory frameworks to be implemented from 2023.